Justiça global e epidemia HIV/AIDS: dos limites da capacidade estatal de viabilizar o acesso a medicamentos essenciais à responsabilidade social das empresas farmacêuticas - Souza, Lucas Silva de (2020)
The debate about the relationship between business and human rights has gradually grown in institutional and doctrinal terms, as well as the recognition that mechanisms to promote the social responsibility of these private actors are lacking. Reflecting on this theme, this dissertation will be limited to the social responsibility of pharmaceutical companies. To this end, the study will be conducted from the perspective of the HIV / AIDS epidemic, as this was the disease that most attracted worldwide attention to the sanitary injustices resulting from the deepening, under the TRIPs agreement, of unequal access to essential medicines. In the face of this scenario, the following question arises: how to balance the interests of innovative companies in drug production with those of peripheral countries after TRIPs? To answer it, it is necessary to reflect on the following questions: what are the institutional causes of unequal access to anti-HIV / AIDS medicines between the social north and south and what are the limits and possibilities of social responsibility of transnational pharmaceutical companies for this inequality? ? In order to answer these questions, the first part of this paper will investigate how global institutional design promotes injustice by disproportionately favoring the spread of the HIV / AIDS epidemic in the global south. To this end, the contradictions of global institutional design and their impact on the unequal access to essential medicines between the social north and south, which propels the violation of rights and hinders the development of human capacities, will be investigated. Later, it will be investigated how Brazil and India mobilized their institutional structure to try to provide medicines to their population. In the second part of the work it will be reflected normatively. Initially, we will investigate the factors that promote the (ir) social responsibility of pharmaceutical companies at institutional level. Next, the doctrinal and institutional construction of CSR will be investigated and the international community's legal response to inequity in access to ARVs will be critically analyzed. Finally, Thomas Pogge's Global Health Impact Fund will be investigated as a possible institutional strategy for reconciling economic and social interests. The study will be approached by dialectical method. Regarding the procedure, it will use the bibliographical and documentary analysis.